Village financial management: Case study in â€œKampung Srerâ€ - Kareth, Vebby; Saerang, David Paul Elia; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2021)
This study aims to analyze village financial management in the special autonomy region, analyze the constraints that hinder village financial management, and analyze efforts to resolve obstacles in village financial management. This study is conducted on the apparatus of Kampung Srer. This study uses a qualitative method with a case study approach and obtains the data through in-depth interviews, documentation, and observation. The results show that the village financial management in the Kampung Srer is partly in accordance with Minister of Home Affairs Regulation (or Permendagri) Number 20 of 2018 concerning the village financial management. The obstacles that hinder the management of village finances in Kampung Srer are political constraints, human resource constraints, and communication problems.Â Efforts made to resolve existing constraints in the management of village finances in Kampung Srer are that the village officials who are selected have the ability that is in accordance with the field of work. There is socialization from the district and district levels related to village financial management activities in the form of increasing the capacity of village officials. There needs to be good coordination for every element in the village community, among village officials, and assistants.